ANALISIS KESALAHAN KOMUNIKASI MATEMATIS SISWA BERGAYA KOGNITIF REFLEKTIF DALAM MENYELESAIKAN MASALAH OPEN-ENDED - Anggraini Eka Pramestasari; Abdur Rahman As'ari; Erry Hidayanto (Jurnal Kajian Pembelajaran Matematika, 2020)
Mathematics is not only related about how to solve problems and provide conclusions, but also as a tool to communicate ideas clearly, precisely and briefly. Through mathematical communication, the teacher can see students'abilities in solving problems. The purpose of this research is to describe the mathematical errors of reflective student communication in solving open-ended problems. The research subjects consisted of 5 students of Boyolangu 1 Junior High School who had reflective cognitive style. Data collection is done by combining the results of data of  mathematical communication test and interviews. The mathematical communication test given is related to triangles and quadrilateral material. Test results were analyzed using mathematical communication indicators, namely: (1) giving clear responses, (2) making diagrams / sketches, (3) communicating mathematical ideas effectively to others, and (4) presenting logical arguments that support answers. The results of data analysis show that students only write some of the completeness of the answers, students are completeless in writing the size of a sketch, students have not conveyed mathematical ideas using complete sentences, and students have not been able to make logical arguments to support students' answers.Keywords: Mathematical communication, reflective cognitive style, open-ended